Prevalence of HIV infection among children with TB and correlation of CD4 cell count level with types of TB - T., Sivabalan; G., Rajkumar (International Journal of Contemporary Pediatrics, 2019)
Background: Tuberculosis (TB) is the second most common cause of death from infectious diseases at the global level, being second only to HIV/AIDS. The present study has been undertaken to find out the prevalence of HIV infection among children with TB and correlation of CD4 cell count level with different types of TB. Methods: This cross-sectional study was carried out in children below 12 years who were diagnosed as having TB, using the modified Kenneth Jones criteria (742 TB infected children) between 2008 and 2010. Descriptive statistics were used to calculate the frequency, mean, median and standard deviation. The linear trend of proportions and trend of chi-square was used to find out the test of association. Results: The HIV prevalence rate among children with Tuberculosis was 9.7%. In TB/HIV coinfection, Pulmonary TB was 44 (61.1%), lymph node TB was 22 (30.6%), Central Nervous System TB was 4 (5.6%), abdominal TB was 1 (1.4%) and spine TB was (1.4%). Pulmonary TB was the most common type is the not significant, mild and advanced grade of immune suppression. CNS tuberculosis was the most common type in the severe grade of immune suppression. CNS TB occurred more commonly in children more than 60 months of age. Lymph node TB is the commonest type of tuberculosis in children with HIV coinfection less than 35 months of age. Conclusions: The prevalence of HIV among tuberculosis children was 9.7%. This prevalence rate indicates the need for routine screening of all newly diagnosed tuberculous children for HIV coinfection.